Optimization of The Portfolio of Financial Institution Pension Funds in Indonesia Using the Response Surface Methodology - Nurahman, Aditya; Widodo, Erwin (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Investments in pension funds consist of government bonds, deposits, bonds, shares, mutual funds, and other investments. Pension funds consist of the Employer Pension Fund (EPF) and the Financial Institution Pension Fund (FIPF). The problem with FIPF is that participants choose investments at the beginning of membership and changes to investment and retirement, so there is a need for research regarding investment placement in FIPF because the average percentage growth in FIPF investments and the average percentage increase in FIPF net worth throughout the 2015–2021 period are the highest. Maximum portfolio placement for each investment, namely government bonds, deposits, bonds, shares, mutual funds, and other investments, which are a combination of independent variables, is the solution for the performance of investment managers at FIPF. In addition, the response variable maximizes the return value and minimizes the standard deviation or risk value to support maximum investment results and determines the maximum portfolio placement of each investment, namely government bonds, deposits, bonds, shares, mutual funds, and other investments, which are free combinations. In the experiment, it is hoped that it can provide alternative literature for investment managers. Apart from knowing the optimal composition of investment placements in FIPF, it is used as a reference for selecting investment packages and for FIPF participants at the start of selecting an investment package and when changing investment packages. The RSM (Response Surface Methodology) method can provide maximum portfolio placement results from each investment: government bonds, bank deposits, corporate bonds, shares, mutual funds, and other investments. Apart from that, the author chose the RSM method because its function is to find out the combination of independent variables to get optimal results, either maximum or minimum, and with an experimental design using several factorial designs that dominate the middle value and points with output in the form of independent variable values and optimal responses previously unknown. The result of this writing is that the maximum return value is 597.294, with the free variable value being the maximization of the return value that supports the maximum return value, such as government bonds = 22.45, deposits = 61.14, bonds = 14.18, shares = 12.76, mutual funds = 5.92, and other investments = 0.46. Based on placement investment and the value of maximization results obtained in the RSM method, which has almost the same results as real data, it proves that the RSM method can confirm the performance behavior of investment managers in FIPF. On the other hand, with the free variable value, the maximum return value is 570.83 and a minimum standard deviation value of 112.38, which is the maximization of the return value, which supports the maximum return value, such as government bonds = 22.45, deposits = 61.14, bonds = 3.49, shares = 2.48, mutual funds = 2.91, and other investments = 0.18. Based on the order and value of the maximization results obtained in the RSM method, the results are almost the same as real data, but by minimizing the standard deviation (risk) value, the percentage of investment placement changes where the placement of bonds, shares, and mutual funds is transferred to deposits and government bonds. This proves that the influence of the minimal standard deviation of the RSM method produces confirmation that is slightly contradictory to the behavior of FIPF investment managers. By using the RSM method in optimizing pension fund investment placement by maximizing the independent variable, the return value reflects the behavior of FIPF pension fund investment managers in half the placement percentage, but in optimizing pension fund investment placement with response variables, maximizing the return value and minimizing the standard deviation (risk) value change the investment placement percentage. By minimizing standard deviation (risk), placements in bonds, shares, and mutual funds are shifted to safe or risk-free assets, namely government bonds and deposits, with the data used from 2015 to 2021 before and during the COVID-19 pandemic. 19, so this research can be used as literature during a crisis, but it is not appropriate to use it during normal conditions